2020
DOI: 10.3847/2041-8213/abbadd
|View full text |Cite
|
Sign up to set email alerts
|

Constraints from Gravitational-wave Detections of Binary Black Hole Mergers on the 12C(α, γ)16O Rate

Abstract: Gravitational-wave detections are starting to allow us to probe the physical processes in the evolution of very massive stars through the imprints they leave on their final remnants. Stellar evolution theory predicts the existence of a gap in the black hole mass distribution at high mass due to the effects of pair instability. Previously, we showed that the location of the gap is robust against model uncertainties, but it does depend sensitively on the uncertain a g C , O 12 16 300. Degeneracies with other mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
176
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(185 citation statements)
references
References 167 publications
9
176
0
Order By: Relevance
“…For example, if the lower edge of the PPSN gap may be modeled as a smooth tapering rather than a sharp cutoff, the feature at m break = 39.7 +20.3 −9.1 may represent the onset of pair-instability. This explanation may pose challenges to our understanding of stellar evolution since the pair-instability cutoff of black-hole masses at ∼ 40 M is thought to be relatively abrupt (Woosley et al 2002;Woosley 2017;Farmer et al 2019), even though its precise location is uncertain (Mapelli et al 2020;Giacobbo et al 2017;van Son et al 2020;Farmer et al 2020;Croon et al 2020;Marchant & Moriya 2020). If the PPSN cutoff is indeed sharp and all observed BBH systems lie below the PPSN gap, the cutoff Law model.…”
Section: Mass Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the lower edge of the PPSN gap may be modeled as a smooth tapering rather than a sharp cutoff, the feature at m break = 39.7 +20.3 −9.1 may represent the onset of pair-instability. This explanation may pose challenges to our understanding of stellar evolution since the pair-instability cutoff of black-hole masses at ∼ 40 M is thought to be relatively abrupt (Woosley et al 2002;Woosley 2017;Farmer et al 2019), even though its precise location is uncertain (Mapelli et al 2020;Giacobbo et al 2017;van Son et al 2020;Farmer et al 2020;Croon et al 2020;Marchant & Moriya 2020). If the PPSN cutoff is indeed sharp and all observed BBH systems lie below the PPSN gap, the cutoff Law model.…”
Section: Mass Distributionmentioning
confidence: 99%
“…must occur at relatively high masses; in the Truncated model, m max = 78.5 +14.1 −9.4 M (or, excluding the most massive event, GW190521, m max = 57.0 +11.9 −6.6 M ). This may have significant implications for nuclear (Farmer et al 2020) 2. We find that λ peak = 0 (which corresponds to no Gaussian peak) is disfavored, supporting the hypothesis that there is a feature in the black hole primary mass spectrum.…”
Section: Mass Distributionmentioning
confidence: 99%
“…Additionally, Marchant & Moriya (2020) investigated the impact of stellar rotation on the location of the mass gap and found that the lower boundary may be shifted upwards by 4-15 per cent depending on the efficiency of angular momentum transport. The boundaries of the pair-instability mass gap have also been proposed as a mechanism to place constraints on nuclear reaction rates (Farmer et al 2020), particle physics (Croon, McDermott & Sakstein 2020), and in cosmological studies (Farr et al 2019).…”
mentioning
confidence: 99%
“…A shorter C-burning phase helps the star to keep a higher entropy, to have a larger migration of the C-burning shell, and hence to end up with a larger O and Si core, affecting its explodability. In that line, let us mention that variations in the 12 C(α, γ ) 16 O reaction can affect the possibility of a low-metallicity star to end up as pair-instability supernova or not and modify the limiting masses for PISN (Takahashi, 2018;Costa et al, 2020;Farmer et al, 2020).…”
Section: Effects Of Nuclear Rates Uncertaintiesmentioning
confidence: 99%